2009
DOI: 10.1080/13658810802475491
|View full text |Cite
|
Sign up to set email alerts
|

A kernel density estimation method for networks, its computational method and a GIS‐based tool

Abstract: We develop a kernel density estimation method for estimating the density of points on a network and implement the method in the GIS environment. This method could be applied to, for instance, finding 'hot spots' of traffic accidents, street crimes or leakages in gas and oil pipe lines. We first show that the application of the ordinary two-dimensional kernel method to density estimation on a network produces biased estimates. Second, we formulate a 'natural' extension of the univariate kernel method to density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
277
0
14

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 386 publications
(291 citation statements)
references
References 26 publications
0
277
0
14
Order By: Relevance
“…However, in analyzing the hot spots of network-constraint events, the assumption of homogeneity of 2-D space does not hold and the relevant KDE methods may produce biased results [9]. Therefore, the planar KDE has been extended to the network KDE, which differs from the planar KDE in several aspects: (i) the network space is used as the point event context; (ii) both search bandwidth r and kernel function k are based on network distance (calculated as the shortest path distance in a network) instead of straight-line Euclidean distance; and (iii) density is measured per linear unit instead of area unit.…”
Section: Contamination In Planar Kde the Space Is Characterized As mentioning
confidence: 99%
See 3 more Smart Citations
“…However, in analyzing the hot spots of network-constraint events, the assumption of homogeneity of 2-D space does not hold and the relevant KDE methods may produce biased results [9]. Therefore, the planar KDE has been extended to the network KDE, which differs from the planar KDE in several aspects: (i) the network space is used as the point event context; (ii) both search bandwidth r and kernel function k are based on network distance (calculated as the shortest path distance in a network) instead of straight-line Euclidean distance; and (iii) density is measured per linear unit instead of area unit.…”
Section: Contamination In Planar Kde the Space Is Characterized As mentioning
confidence: 99%
“…The cell size depends on the user choice and the dataset. Okabe et al [9] suggested using a cell size of (r/10) as a rule of thumb.…”
Section: Planar Kernel Density Estimationmentioning
confidence: 99%
See 2 more Smart Citations
“…[18] suggests the use of general density distributions, from which random samples are generated, yielding a discrete approximation to the problem, which is the one which is later analyzed. Statistical kernel methods have also been recently proposed to model the demand, [20,23], though, as far as the authors know, no optimization has been carried out, excepting, as said above, discretization via simulation.…”
Section: Introductionmentioning
confidence: 99%